Environmental Contamination as a Risk Factor for Intra-Household Staphylococcus aureus Transmission - Knox, Justin; Uhlemann, Anne-Catrin; Miller, Maureen; Hafer, Cory; Vasquez, Glenny; Vavagiakis, Peter; Shi, Qiuhu; Lowy, Franklin D. (PloS one, 2012)
The household is a recognized community reservoir for Staphylococcus aureus. This study investigated potential risk factors for intra-household S. aureus transmission, including the contribution of environmental contamination. We investigated intra-household S. aureus transmission using a sample of multiple member households from a community-based case-control study examining risk factors for CA-MRSA infection conducted in Northern Manhattan. During a home visit, index subjects completed a questionnaire. All consenting household members were swabbed, as were standardized environmental household items. Swabs were cultured for S. aureus. Positive isolates underwent further molecular characterization. Intra-household transmission was defined as having identical strains among two or more household members. Multiple logistic regression was used to identify independent risk factors for transmission. We enrolled 291 households: 146 index cases, 145 index controls and 687 of their household contacts. The majority of indexes were Hispanic (85%), low income (74%), and female (67%), with a mean age of 31 (range 1-79). The average size of case and control households was 4 people. S. aureus colonized individuals in 62% of households and contaminated the environment in 54% of households. USA300 was the predominant clinical infection, colonizing and environmental strain. Eighty-one households had evidence of intra-household transmission: 55 (38%) case and 26 (18%) control households (P<.01). Environmental contamination with a colonizing or clinical infection strain (aOR: 5.4 [2.9-10.3] P<.01) and the presence of a child under 5 (aOR: 2.3 [1.2-4.5] P = .02) were independently associated with transmission. In separate multivariable models, environmental contamination was associated with transmission among case (aOR 3.3, p<.01) and control households (aOR 27.2, p<.01). Environmental contamination with a colonizing or clinical infection strain was significantly and independently associated with transmission in a large community-based sample. Environmental contamination should be considered when treating S. aureus infections, particularly among households with multiple infected members.